THE ROLE OF INDIVIDUAL AND COMMUNITY FACTORS ON THE USE OF LONG-TERM CONTRACEPTIVE METHODS (MKJP) ON WOMEN OF REPRODUCTIVE AGE COUPLES IN INDONESIA 2018 - Vernonia Yora Saki; Ema Novita Deniati; Besral Besral; Mario Ekoriano (The Indonesian Journal of Public Health, 2021)
ABSTRACTThis research discussed the role of individual and community factors on the use of Long Term Contraceptive Method (MKJP) in women of reproductive age couple by region in Indonesia in 2017. The study design follows the advanced analysis design of RPJMN BKKBN survey data that was cross-sectional design. The sample of research on RPJMN survey was women of reproductive age couple. Data were analyzed by Multilevel Logistic Regression analysis. The results showed that the Proportion of women of reproductive age couples using long-term contraceptive methods (MKJP) in Java Bali (27.2%) more than high than Outside of Java Bali I (22.9%) and Outside of Java Bali II (20.2%). Multilevel analysis results showed that there are variations between provinces of MKJP used in women of reproductive age couple in the area of Indonesia Java Bali and Outside of Java Bali I of 1.4 and 1.3 in the area of Outside of Java Bali II. Based on the results, BKKBN recommended implementing MKJP usage program that takes into account the area aspect and cannot be uniform for all provinces in Indonesia. Keywords: Contraception MKJP, Women WUS